ANALISIS GENDER DALAM NOVEL DWILOGI BERKISAR MERAH KARYA AHMAD TOHARI - Purnamasari, Lilis Indah; Priyadi, A. Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe reason the authors chose gender analysis is because the author wants to analyze gender on the main character by using gender prejudices and gender injustices that are influenced by the environment. The research problems revealed by the authors are (1) Gender prejudice in the Dwilogi Ranged novel by Ahmad Tohari. (2) gender inequality in the Dwilogi Ranges novel by Ahmad Tohari. The method used in this research is descriptive qualitative method, with approach of feminism study. The data in this study are sentences or quotations containing the main character's gender analysis. The technique of data collection using documentary study with key instrument is the author. Based on the results of existing data analysis, the research results show gender analysis on the main character of gender prejudice that is gender, age ,. Skin color is a natural view that is easy to see. People assume that female gender is a kind of class in the social layer. Adat views women as being inferior to men, so it is not surprising that society considers women to be slaves. While the gender inequality is marginalization, subordination, and streotipe.Key words: Main Character Conflict, Novel.